PKM : Pelatihan Desain Kemasan Produk Umkm Desa Tarikolot Berstandar PIRT - Odi Nurdiawan; Nana Suarna; Dadang Sudrajat; Maria Dewanty Rafu; Muhammad Zeya Sebastian (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (PKM) titled "Training on PIRT Standardized Product Packaging Design for UMKM in Tarikolot Village" aims to improve the quality of product packaging for UMKM (Micro, Small, and Medium Enterprises) in Tarikolot Village to meet PIRT (Home Industry Food) standards. Good packaging not only protects the product but also enhances its attractiveness and market value. The problem faced by UMKM in Tarikolot Village is that their product packaging design often does not meet PIRT standards. As a result, their products are less appealing to consumers and face difficulties in obtaining permits and marketing. Non-standard packaging design also impacts the quality and safety of the food produced. The purpose of this training is to enhance the skills of UMKM in designing product packaging that meets PIRT standards, making their products more marketable and compliant with food safety regulations. Additionally, this training aims to increase awareness of the importance of good packaging in product marketing. The training is conducted in several sessions, covering both theory and practice. The theory sessions provide basic knowledge about PIRT standards and the principles of good packaging design. The practical sessions involve workshops where participants directly design their product packaging under the guidance of packaging design experts. The training materials also include printing techniques and the selection of suitable packaging materials. Following the training, participants showed significant improvement in their packaging design capabilities. Most UMKM products in Tarikolot Village now meet PIRT standards, with more attractive and informative packaging designs. Participants also reported increased knowledge of packaging regulations and the application of effective design techniques. Thus, this training has successfully improved the quality of UMKM products in the village and opened up new marketing opportunities.